Comparative toxicity of essential oil and blends of selected terpenes of Ocotea species from Pernambuco, Brazil, against Tetranychus urticae Koch - MARCILIO M. DE MORAES (Anais da Academia Brasileira de Ciências)
ABSTRACT Essential oils from the leaves of two species of the genus Ocotea that occur in the Atlantic Forest in the state of Pernambuco, Brazil, were analyzed using gas chromatography-mass spectrometry. The acaricidal activity of these oils as well as 11 selected components and blends were evaluated in fumigation and residual contact tests against the two-spotted spider mite (Tetranychus urticae). Sixty-seven constituents were identified, totaling 97.3 ± 0.3% and 97.8 ± 0.5% of the oils from O. duckei and O. glomerata, respectively. Sesquiterpene was the dominant class. The compounds β-caryophyllene (18.6 ± 0.1%) and aromadendrene (17.3 ± 0.6%) were the main constituents of the oils from O. duckei and O. glomerata, respectively. Acaricidal action varied depending on the method employed, species and chemical nature of the selected constituents. The mites were susceptible to the oils and chemical constituents using the fumigation method. The O. duckei oil was respectively 2.5-fold and 1.5-fold more toxic than the O. glomerata oil using the fumigation and residual contact methods. Among the selected constituents, β-caryophyllene was the most toxic, independently of the method employed. The individual toxicity of the selected compounds and their blends as well as the role of these constituents in the overall toxicity of the essential oils are also discussed.